The Role of Bcl-2 Family Proteins in Therapy Responses of Malignant Astrocytic Gliomas: Bcl2L12 and Beyond - Fotini M. Kouri; Samuel A. Jensen; Alexander H. Stegh (The Scientific World Journal)
Glioblastoma (GBM) is a highly aggressive and lethal brain cancer with a median survival of less than two years after diagnosis. Hallmarks of GBM tumors include soaring proliferative indices, high levels of angiogenesis, diffuse invasion into normal brain parenchyma, resistance toward therapy-induced apoptosis, and pseudopallisading necrosis. Despite the recent advances in neurosurgery, radiation therapy, and the development of targeted chemotherapeutic regimes, GBM remains one of the deadliest types of cancer. Particularly, the alkylating agent temozolomide (TMZ) in combination with radiation therapy prolonged patient survival only marginally, and clinical studies assessing efficacies of targeted therapies, foremost ATP mimetics inhibiting the activity of receptor tyrosine kinases (RTKs), revealed only few initial responders; tumor recurrence is nearly universal, and salvage therapies to combat such progression remain ineffective. Consequently, myriad preclinical and clinical studies began to define the molecular mechanisms underlying therapy resistance of GBM tumors, and pointed to the Bcl-2 protein family, in particular the atypical member Bcl2-Like 12 (Bcl2L12), as important regulators of therapy-induced cell death. This review will discuss the multi-faceted modi operandi of Bcl-2 family proteins, describe their roles in therapy resistance of malignant glioma, and outline current and future drug development efforts to therapeutically target Bcl-2 proteins.